APRM-UN CEPA Principles Program for effective governance of SDGs and Agenda 2063 : lessons learnt and Challenges (African Journal of Public Administration & Management, 2026)
The APRM was launched on 09 March 2003 by the NEPAD Heads of State andGovernment What is the APRM?Implementation Committee (HSGIC) in Abuja,Nigeria (NEPAD/HSGIC/03-2003/APRM/MOU (09 March 2003), as a self-monitoring instrument voluntarily acceded to by member states of the African Union.▪ The APRM is an African-owned and African-led platform for self-assessment, peer-learning, and experience-sharing with the purpose of promoting democratic governance, high economic growth, sustainable development and accelerated regional and continental economic integration.▪ Since 2017, the AU Assembly has expanded the mission of the APRM to include:i) Tracking the implementation, monitoring and evaluation of Agenda 2063and SDGsii) Developing Africa Governance Report every 2 years in collaboration withAGA and APSAiii) Supporting Member States in the field of Credit Rating Agencies.iv) To position the APRM as an early warning tool for conflict prevention onthe continent, in the context of harmony and synergy between the APRM,the African Peace and Security Architecture, and the African GovernanceArchitecture